The effects of parental antisocial behavior trait and parenting practices on child adjustment: a study of single-mother families - Davis, Jacqueline Marie (1993)
The purpose of this study is to examine the effects of parental antisocial behavior trait on child adjustment. The literature (Patterson and Capaldi, 1991) suggests that antisocial parents are at significantly greater risks for a variety of problems, such as unskilled parenting practices and stressful life events (e.g., marital transitions and unemployment). The author employs social learning and exchange principles. The data for this study were taken from the first year of a three-year panel study conducted by the Center for Family Research and Rural Mental Health at Iowa State University. The data consist of 210 single-mother families in the state of Iowa. These data were analyzed using multivariate analyses. This study is important because the participants were selected on the basis of divorce in the parents rather than conduct disorder in the children. Thus, the data is free of referral biases unlike the data of previous studies in this area. Also, previous models have been limited to conduct disorders in boys only. The data employed in this study allow for gender analyses, as well as an analysis of paternal effects on child antisocial behavior. Findings show that family income, mother's education, mother's and father's parenting practices and father's antisocial behavior trait are prime determinants of child adjustment problems